Effect of synthetic route on morphology of zinc oxide and cadmium doped zinc oxide nanomaterials. (2022) - Perundevi, T.S.; Karthika, A.; Ramalakshmi, S.
Abstract: In the current research, zinc oxide (ZnO) and cadmium doped ZnO nanoparticles (Cd-ZnO) were synthesized by hydrothermal and ultrasonication method utilising CTAB (cetyltrimethyl ammonium bromide), a cationic surfactant. The morphology and nature of crystal lattice of synthesized ZnO and Cd-ZnO nanoparticles were screened by SEM and XRD analysis. Effect of method of synthesis and dopant on the surface morphology of ZnO nanoparticles was studied. SEM studies showed the formation of ZnO nanorods (∼30–57 nm) through hydrothermal method, and nanograins (∼37–53 nm) via ultrasonication. For Cd-ZnO a vast difference was observed in the surface topography. Among the two mentioned methods Cd-ZnO nanoflakes were obtained by ultrasonication (∼100 nm) whereas hydrothermally derived Cd-ZnO was resulted as agglomerated nanorods of about 50 to 100 nm. XRD analysis also supported the results. Hence, it was shown that both the mode of synthesis has a significant effect and process of doping has a remarkable effect on the surface morphology of the ZnO nanoparticles.